2011
DOI: 10.1021/bi200063a
|View full text |Cite
|
Sign up to set email alerts
|

Challenges and Advances in Validating Enzyme Design Proposals: The Case of Kemp Eliminase Catalysis

Abstract: One of the fundamental challenges in biotechnology and biochemistry is the ability to design effective enzymes. Despite recent progress, most of the advances on this front have been made by placing the reacting fragments in the proper places, rather than by optimizing the preorganization of the environment, which is the key factor in enzyme catalysis. Thus, rational improvement of the preorganization would require approaches capable of evaluating reliably the actual catalytic effect. This work considers the ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
117
0
3

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 78 publications
(129 citation statements)
references
References 45 publications
7
117
0
3
Order By: Relevance
“…Warshel et al 2006b and references cited therein), but also the effects that mutations are observed to have on the catalysis (as has been done in countless computational studies on a wide range of systems, see e.g. Frushicheva et al 2011 ;Liu & Warshel, 2007 ;Roca et al 2009 ;Shurki & Warshel, 2004). This is the only way one can not only characterize the mechanism of the enzyme-catalyzed reactions, but also understand the molecular basis for the observed effect.…”
Section: What Is the Actual Mechanism Of Phosphate Hydrolysis And Relmentioning
confidence: 98%
See 1 more Smart Citation
“…Warshel et al 2006b and references cited therein), but also the effects that mutations are observed to have on the catalysis (as has been done in countless computational studies on a wide range of systems, see e.g. Frushicheva et al 2011 ;Liu & Warshel, 2007 ;Roca et al 2009 ;Shurki & Warshel, 2004). This is the only way one can not only characterize the mechanism of the enzyme-catalyzed reactions, but also understand the molecular basis for the observed effect.…”
Section: What Is the Actual Mechanism Of Phosphate Hydrolysis And Relmentioning
confidence: 98%
“…Of course, the difference between our approach and the qualitative approach promoted by e.g. (Lassila et al 2011) can also be realized by the fact that we have been actually able to reproduce the effect of different mutations Frushicheva et al 2011 ;Liu & Warshel, 2007 ;Roca et al 2009 ;Shurki & Warshel, 2004), whereas (Lassila et al 2011) could only argue that they suggested the direction of the effect of the Arg finger, without being able to even hint at what the magnitude of those effects may be, and were also forced to invoke factors such as water positioning, thereby overlooking the key effect of the P-loop and the Mg 2+ ion, as well as the fact that catalysis by water positioning has long been shown to have only a minor catalytic effect (both as NAC and as an entropic effect, see discussion in Warshel et al 2006b and references cited therein).…”
Section: Mechanistic Insights Into Phosphate Hydrolysis In Proteinsmentioning
confidence: 99%
“…So arguing that such approaches cannot predict the activity of altered enzymes is one of the most problematic parts of the SABW paper. The fact is that we have repeatedly predicted the activity of countless altered enzymes [24,[51][52][53], and we are not aware of any such prediction based on the dynamical concepts promoted by SABW and others. We would also like to clarify that it is easy to imply that all calculations are important in order to understand catalysis, and that this might be popular in some circles.…”
Section: On the Need Of Calculations Of Many Effectsmentioning
confidence: 98%
“…EVB is based on a semiempirical Hamiltonian which describes reactants and products with their resonance structure (explicitly defining atom connectivity). Although EVB energies are less accurate than ab initio and DFT QM/MM methods, free energy calculations are orders of magnitude quicker and still can achieve accurate results [183,184], making EVB a suitable tool to score a bigger number of mutants.…”
Section: Catalytic Rate Constant Enhancementmentioning
confidence: 99%